Cytokine evaluation in untreated and radioimmunotherapy-treated tumors in an immunocompetent rat model - Erika Elgström; Tomas G Ohlsson; Sophie E Eriksson (Tumor Biology)
The tumor microenvironment can act so as to stimulate or reject tumor cells. Among the determining factors are cytokines produced, for example, by infiltrating immune cells, tumor cells, and fibroblasts. External radiotherapy has been shown to be able to activate an immune response against tumor cells with cytokine signaling as an important part of the activation. The aim of this study was to evaluate the cytokines present in the tumor microenvironment and whether the cytokine profile changed during tumor regression induced by radioimmunotherapy with the beta emitter 177 Lu. Immunocompetent rats with colon carcinoma tumors were injected with 400 MBq/kg 177 Lu-mAb, and the tumors were excised after 1, 2, 3, 4, 6, or 8 days post injection (4 rats/day on days 1–6 and 8 rats on day 8). Tumors from 10 untreated rats were used as control tissue. The tumors were divided into half: one half was prepared for cytokine analysis with a cytokine array kit and the other half was used for histological analysis. A total of 18 of the 29 cytokines evaluated were detected in this tumor model, and the majority of these act in a pro-inflammatory manner or stimulate the infiltration of immune cells. The differences between treated tumors and control tumors were small, thus the cytokine profile in the untreated tumors did not transfer to an anti-inflammatory profile during tumor regression induced by radioimmunotherapy with 177 Lu. Histological evaluation demonstrated a heterogeneous pattern of ongoing cell death and the formation of granulation tissue.